2005
DOI: 10.1177/10253823050120030111x
|View full text |Cite
|
Sign up to set email alerts
|

Public health policies as guides for local public policies: the experience of Sobral-Ceará, Brazil

Abstract: Abstract:The accelerated urbanisation process that Brazil has gone through in the last 50 years has given rise to daunting challenges for public managers, especially in terms of local public policy management for the building of "healthy cities". In Sobral, a municipality of 173,000 inhabitants in Ceará in the North-eastern region of Brazil, a number of municipal policies were initiated beginning in 1997, many in partnership with the federal and state governments. They were inspired by the vision of a healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…According to the OECD classification, five studies reported data from a large metropolitan area ( 28 , 31 , 37 , 38 , 41 ). Sobral, Richmond, Rennes, Bristol, Ljubljana and Sosnowiec were classified as medium-sized urban areas ( 27 , 30 , 32 , 42 ); Barcelona, San Francisco, Lisbon, Detroit and Amsterdam were classified as metropolitan areas ( 33 , 36 , 40 , 42 ); and Noarlunga, Gulfport, Hermosa Beach, Redondo Beach and Manhattan Beach as small-size urban areas ( 29 , 34 , 43 ). Matsapha and Vancouver were classified as other urban settings ( 35 , 39 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the OECD classification, five studies reported data from a large metropolitan area ( 28 , 31 , 37 , 38 , 41 ). Sobral, Richmond, Rennes, Bristol, Ljubljana and Sosnowiec were classified as medium-sized urban areas ( 27 , 30 , 32 , 42 ); Barcelona, San Francisco, Lisbon, Detroit and Amsterdam were classified as metropolitan areas ( 33 , 36 , 40 , 42 ); and Noarlunga, Gulfport, Hermosa Beach, Redondo Beach and Manhattan Beach as small-size urban areas ( 29 , 34 , 43 ). Matsapha and Vancouver were classified as other urban settings ( 35 , 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…As a lone process, multisectoral action to advance the construction of a healthy city was addressed in six (35%) studies ( 30 32 , 35 , 36 , 41 ). Five studies assessed both multisectoral action and health governance ( 27 , 29 , 33 , 38 , 39 ); three reported data on multisectoral action and civic engagement ( 34 , 37 , 40 ), and the same amount of studies assessed only civic engagement ( 28 , 42 , 43 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The final intervention demonstrated the impact of utilizing a multifaceted approach incorporating strategies from all Three E’s on VRU deaths in Brazil ( Monteiro Andrade et al, 2005 ). In 2005, Monteiro Andrade and colleagues documented a multifaceted urban development policy implemented in Sobral-Ceará, Brazil in 1997.…”
Section: Resultsmentioning
confidence: 99%